High simple carbohydrate intake and its impact on growth biomarkers and stunting risk in early childhood - Yessi Alza; Lily Restusari; Aslis Wirda Hayati; Agustina Indri Hapsari; Dewi Purwaningsih (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Stunting in early childhood remains a major public health issue in developing countries, including Indonesia. In addition to undernutrition, excessive intake of simple carbohydrates may disrupt the endocrine pathways crucial for linear growth. This study examined the association between simple carbohydrate consumption and growth biomarkers insulin-like growth factor 1 (IGF-1), leptin, and growth hormone as predictors of stunting risk in children aged 12–36 months of age. A cross-sectional observational study was conducted with 250 children from urban and rural settings. Dietary intake was assessed using a validated 24-hour recall, and biomarker levels were measured using ELISA. The results showed an average daily energy intake of 1,350 kcal, with 65% derived from carbohydrates, predominantly simple sugars and refined starches. Stunted children exhibited significantly lower concentrations of IGF-1, leptin, and growth hormone (p < 0.01), with strong inverse correlations between simple carbohydrate intake and biomarker levels (r = –0.45 for IGF-1; r = –0.38 for growth hormone [GH]). Multiple regression analysis confirmed that a higher intake of simple carbohydrates significantly predicted lower biomarker levels and reduced height-for-age z-scores (HAZ). These findings highlight the importance of dietary quality, emphasizing the need to reduce simple carbohydrate intake to support hormonal balance and optimal linear growth in early childhood.